Macroeconomic Issues and Policies in the Middle East and North Africa. (Washington, D.C. : International Monetary Fund, 2001)
This book brings together recent IMF research on how the Middle East and North African countries are grappling with various macroeconomic challenges. It rigorously analyzes policy alternatives for a range of relevant topics, including the implications of changing demographic trends for growth and unemployment, determinants of inflation, financial-sector reform and Islamic banking, fiscal sustainability in oil-dependent economies, exchange rate and trade arrangements, and impediments to foreign direct investment. The book's overall theme-self-sustaining and faster growth can be achieved through comprehensive structural reforms and closer collaboration between the region's policymakers and the international community.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet